Mixed-ligand Complexes of Ruthenium(II) and Iridium(III) with Triphenylphosphine and Thiocarbohydrazide - Pandey, R.N.; Gautam, K.V. (Asian Journal of Chemistry, 2011)
The ligand substitution reactions in precursor complexes [Ru(Pϕ3)4Cl2], [RuH(CO)(Pϕ3)3Cl] and [Ir(CO)(Pϕ3)2Cl] are reported using thiocaorbohydrazide as ligand. The solid products isolated after ligand displacement reaction in [Ir(CO)(Pϕ3)2Cl] are further undergo oxidativeaddition easily with ethanolic HCl leading to the formation of other iridium(III) complexes. All complexes are characterized by elemental analysis, IR, UV-VIS, 1H NMR, molar cunductivity and magnetic susceptibility data. Probable octahedral structure of ruthenium(II) and iridum(III) complexes are reasonably assigned.